Edukasi Penggunaan Maskes Pada Pasien Yang Berkunjung Ke Rumah Sakit dr. Zainal Abidin Kota Banda Aceh - Salfiyadi, Teuku; Yusna, Nurul; Cut Sirri Mulyati (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The government advises the public to adhere to health protocols to prevent the spread of COVID-19. But in reality, there are still people who carry out activities outside the home without wearing a mask or wearing a mask but placing it on their chin without covering their nose and ears. The use of masks that are not good will increase the risk of transmission of COVID-19. This is what encourages the community service team to increase community knowledge and behavior about the correct use of masks and also through health education activities specifically for high-risk groups such as teenagers, pregnant women, mothers with toddlers, and the elderly. This service uses the Healthy Education method as an effort to provide information about the importance of maintaining health as one of the ways to prevent the transmission of COVID-19. The number of samples that were educated was 1.000.000 people who visited the Dr. Zainal Abidin General Hospital, Banda Aceh City. Keywords: Education and Masks